A digital precedent library for classical period Ottoman mosques. (1st January 2013) - Tunçer, Bige
We have developed a digital environment and a method for the analysis, structuring and presentation of architectural information on classical period Ottoman mosques designed and engineered by the great architect Sinan. This environment and method is targeted at architects and architecture students, architectural historians, scholars, and public interested in classical period Ottoman mosque architecture. The research aims at developing a taxonomy for the classification of the components and aspects describing this architecture and its era, to be used and extended by the target group. Another research goal is to implement a flexible and extensible environment that utilises this taxonomy for the analysis and presentation of this body of architecture. The environment enables the creation and navigation of relationships between information entities enabling associative browsing and creative discoveries. This environment is designed to be accessible online, and can be extended to become an online knowledge centre for classical period Ottoman mosques.